Interleukin-10 induces expression of CD39 on CD8+T cells to potentiate anti-PD1 efficacy in EGFR-mutated non-small cell lung cancer - Lei Cheng; Caicun Zhou; Tao Jiang; Fei Zhou; Shengxiang Ren; Hongcheng Liu; Xinyu Liu; Xiaoxia Chen; Xuefei Li; Chao Zhao; Meng Qiao; Haowei Wang; et al. (Journal for ImmunoTherapy of Cancer)
Background Anti-PD-1(L1) therapies are less efficacious in patients with EGFR-mutated non-small-cell lung cancer. However, the underlying mechanism is poorly understood.Methods The characteristics of T cells in EGFR-mutated and wild-type tumors were analyzed based on The Cancer Genome Atlas database and clinical samples. Plasma levels of 8 T-cell-related cytokines were evaluated and its association with immunotherapy efficacy were explored. Association between EGFR signaling pathway and IL-10 was examined through tumor cell lines and clinical tumor samples. In vitro restimulation model of human CD8+T cells isolated from peripheral blood was used to analyze the impact of IL-10 on T cells. Doxycycline-inducible transgenic EGFRL858R mouse models were used to investigate the efficacy of combining recombinant mouse IL-10 protein and PD-1 blockade and its underlying mechanism in vivo.Results EGFR-mutated tumors showed a lack of CD8+T cell infiltration and impaired CD8+T cell cytotoxic function. The incompetent CD8+T cells in EGFR-mutated tumors were characterized as absence of CD39 expression, which defined hallmarks of cytotoxic and exhausted features and could not be reinvigorated by anti-PD-1(L1) treatment. Instead, CD39 expression defined functional states of CD8+T cells and was associated with the therapeutic response of anti-PD-1(L1) therapies. Mechanically, IL-10 upregulated CD39 expression and was limited in EGFR-mutated tumors. IL-10 induced hallmarks of CD8+T cells immunity in CD39-dependent manner. Using autochthonous EGFRL858R-driven lung cancer mouse models, combining recombinant mouse IL-10 protein and PD-1 blockade optimized antitumor effects in EGFR-mutated lung tumors.Conclusions Our study suggested that owing to low level of IL-10 to induce the expression of CD39 on CD8+T cells, fewer phenotypically cytotoxic and exhausted CD39+CD8+T cells in EGFR-mutated tumors could be potentially reinvigorated by anti-PD-1(L1) treatment. Hence, IL-10 could potentially serve as a cytokine-based strategy to enhance efficacy of anti-PD-1(L1) treatment in EGFR-mutated tumors.